A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

A knowledge-informed data-efficient framework for soil correlation modelling - Pin Zhang; Gang Yang (Computers and Geotechnics, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Synergistic microbubble ozonation and CaO2 activation for refinery sludge valorization: Organic carbon liberation and petroleum hydrocarbon degradation - Di Shu; Ziyang Lou; Kaiyan Yang; Zhiyi Sun; Hui Wang; Zhaowen Cheng; Pin Zhou; Shuping Zhang; Nanwen Zhu; Luochun Wang (Journal of Environmental Management, 2026)

Poly(lactic-co-glycolic acid) (PLGA)-based vaccine delivery systems for fish: physicochemical properties, immunological mechanisms, and applications - Shu-Chun Chuang; Yi-Chen Lin; Ya-Shuan Chou; Shang-Pin Liu; Shao-Wen Hung; Ti-Chun Chang; Chung-Hwan Chen; Chung-Da Yang (Fish & Shellfish Immunology, 2026)

Effects of N-carbamylglutamate supplementation on growth, serum biochemistry, antioxidant capacity, immune function, hormonal profile, and reproductive performance in rabbits under chronic heat stress conditions - Pin Zhai; Jie Yang; Feng Qin; Yao Yao; Le Shao; Jian Li; Xia Zhang (Animal Reproduction Science, 2026)

Cordycepin-mediated protection against bisphenol A–induced male reproductive toxicity via PI3K/mTOR/HIF-1α signaling - Wenjuan Yang; Jiang Guo; Zhaorui Shuai; Shuai Han; Xuguang Jing; Hui Long; Nan Li; Yanni Zhao; Pin Gong; Yuxi Guo (Food Research International, 2026)

Age-stratified genomic analyses reveal population-specific genetic determinants of exceptional longevity in Taiwan - Ming-Shun Hsieh; Shu-Min Yang; Shu-Hui Liao; Chayanika Goswami; Pei-Hsuan Wu; Tzu-Hung Hsiao; Yi-Ming Chen; Sung-Yuan Hu; Chorng-Kuang How; Tzu-Pin Lu; Amrita Chattopadhyay (GeroScience, 2026)

Diversified rotation reduced N2O emissions by shaping N-cycling microbial communities and increasing their network complexity - Taobing Yu; Lang Cheng; Pin Wang; Lei Yang; Tengxiang Lian; Huadong Zang; Zhaohai Zeng; Yadong Yang (Journal of Environmental Sciences, 2026)

Sea buckthorn for future foods: bioactive mechanisms, synthetic biology, and precision delivery systems - Nan Li; Peidong Fan; Lulu Wang; Luole Feng; Hui Long; Wenjuan Yang; Jing Wang; Yanni Zhao; Huan Liu; Yuxi Guo; Pin Gong (Food Research International, 2026)

Immunomodulatory mechanism of Pleurotus eryngii polysaccharides in acrylamide-induced mice via the P2X7-NLRP3 pathway, metabolic homeostasis and gut microbiota - Jing Wang; Xiuxiu Liu; Dongliang Jin; Man Wang; Nan Zhang; Yanni Zhao; Wenjuan Yang; Nan Li; Xuefeng Chen; Pin Gong (Food Bioscience, 2026)

Widely targeted metabolomics reveals chemical mechanism of bloating in Rosa roxburghii Tratt juice induced by vitamin C and its chiral isomers - Hong Yang; Yuting Liu; Xinying Wang; Wenxin Zhang; Bo Peng; Dalong Chen; Angze Gao; Weixin Huang; Pin Qian; Deshun Yu; Yifu Tian; Xianzhi Dong (Food Chemistry, 2026)

Ophiocordyceps Polyrhachicola (Hypocreales, Ophiocordycipitaceae), a New Species of Ant Associated Fungal Parasite in China - Jia‐Ping Wang; Chada Norphanphoun; Yu Yang; Yuan‐Pin Xiao; Kevin D. Hyde; Yong Wang (New Zealand Journal of Botany, 2026)
Ophiocordyceps , the largest genus within the family Ophiocordycipitaceae, is known for its parasitism on many insect hosts. Recent advances in global biodiversity research have enhanced the classification and ecological understanding of this genus, underscoring its pivotal role in global ecosystems. As the type genus of Ophiocordycipitaceae, Ophiocordyceps has undergone extensive taxonomic revision based on comprehensive studies. In this study, Ophiocordyceps polyrhachicola , a novel species from China that parasitizes the ants of the genus Polyrhachis inhabiting leaf litter of temperate deciduous forests is introduced. Species placement is supported corroborated by morphological observations and phylogenetic analyses of a multi‐locus dataset comprising ITS, LSU, SSU, rpb1 , rpb2 , and tef1‐α sequences. Detailed comparisons with closely related taxa reveal distinctive morphological traits and molecular characteristics, establishing O. polyrhachicola as a unique and well‐delimited species within the genus.

Oral vaccination via virus-like particles encapsulated in Lactococcus lactis - Hui Yee Hong; Lee Ching Pei Carmen; Pin Xuan Chee; Lim Xin Ying; Zhi Wei Wong; Janlin Chan; Mookkan Prabakaran; Daiwen Yang (Fish & Shellfish Immunology, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

Analysis of insertion/deletion variation of litter size in Guizhou black goat - Yang Yang; Yan Pin Zhao; Yong Han (Tropical Animal Health and Production, 2025)

Dietary Supplementation with Multi-strain Probiotic Formulation (Bifidobacterium B8101, Lactobacillus L8603, Saccharomyces bayanus S9308, and Enterococcus SF9301), Betaine or their Combination Promotes Growth Performance Via Improving Intestinal Development in Broilers - Dan Hu; Xiaoting Wu; Pin Song; Manman Hou; Li’an Pan; Xiaoran Yang; Qinwei Sun; Yingdong Ni (Probiotics and Antimicrobial Proteins, 2025)

Novel insights into the effect of sTIM-3 on NLRP3 inflammasome via interacting with ASC - Xiaodi Zhang; Na Han; Ziqing Xu; Zheng Tong; Xiaolei Ren; Yang Sun; Chunyang Li; Xuetian Yue; Zhuanchang Wu; Xiaohong Liang; Chunhong Ma; Pin Wang; et al. (Inflammation Research, 2025)

Fluorescent visualization of endoplasmic reticulum stress induced by microplastic pollution via surge of intracellular reactive oxygen species - Le Yang; Xinchao Xia; Fan Li; Qiuhong Mo; Pin Shang; Junbin Li; Yi Li; Yibo Zhou; Zhihe Qing (Analytica Chimica Acta, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Microplastics provide new niches for nitrifiers to maintain nitrification performance in nitrifying bioreactors - Peikun Yuan; Yang Wang; Yipeng Lu; Zheng Wei; Pin Gao (Environmental Research, 2025)

Electroactive biofilm enhances synergistic degradation of sulfamethoxazole and roxarsone in actual livestock wastewater: extracellular electron transfer drives metabolic network remodeling - Pin Peng; Xinyu Yan; Lixiang Chen; Xiang Li; Huiying Yang; Yijing Miao; Feng Zhao (Environmental Research, 2025)

Acid-activated hexagonal boron nitride efficiently accelerates the photocatalytic decomposition of perfluoroalkyl substances: the mediation of chlorine radical - Yi-Chin Hsieh; Ming-Han Yang; Pin-Fei Chu; Chia-Hsuan Kao; Paul Westerhoff; Wen-Che Hou (Chemical Engineering Journal, 2025)

Injectable GelMA–PEDOT:PSS conductive hydrogel for cardiac-tissue engineering and integrated organic electrochemical transistor–based bioelectronic patch for biosensing and controlled extracellular vesicle release - Chung-Chuan Chou; Yu-Sheng Hsiao; Ming-Fu Hou; Pin-Yu Zhang; Min-Yu Hsieh; Lin-Yang Weng (Chemical Engineering Journal, 2025)

Three-dimensional material point analysis of the Guanghua landslide influenced by topographic constraints - Yi-Pin Peng; Kuo-Hsin Yang; Wei-Lin Lee; Tatag Yufitra Rus; Shih-Hao Cheng; Jyun-Yen Wang; Chihping Kuo (Landslides, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

Identification, occurrence, and toxicity prediction of alkylphenolic disinfection by-products in disinfected combined sewer overflows - Yayun Zhang; Pin Wang; Rong Xiao; Wenyuan Yang; Fang Yuan Jiang; Wen Hai Chu (Journal of Hazardous Materials, 2025)

Salinity-dependent responses differentiate branchial ion regulation during acute hypothermal stress in euryhaline Indian Medaka - Naveen Ranasinghe; Salman Akram; Shi-Shien Lee; Pin-Jhu Liao; Tsung-Jui Yang; Yu-Chieh Kung; Tsung-Han Lee; Chia-Jui Liu (Fish Physiology and Biochemistry, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

A new benzoquinone and a new dihydroflavone from Fissistigma polyanthum and their bioactivity - Jian-Fen Xiao; Ming-Rui Yang; Pin-Xiang Fu; Rui Yang; Hong-Ping He; Hua-Yi Jiang (Phytochemistry Letters, 2025)

Upregulation of circRNA_0002286 protects against brain ischemia/reperfusion injury after remote ischemic postconditioning via microRNA-124-3p/VLCAD axis - Chun-Yan Li; Wei Ma; Jin-Wei Yang; Wei Liu; Kuang-Pin Liu; Xiao-Hua Weng; Shou-Rui Niu; Shen Li; Jian-Hui Guo; Li-Yan Li (Journal of Molecular Histology, 2025)

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

Investigation of the thermal response of an energy raft foundation in Taipei - Ignatius Tommy Pratama; Josiane Jello; Xin-Bai Mao; Kuo-Hsin Yang; Jui-Pin Tsai; Tugce Baser; Chihping Kuo (Tunnelling and Underground Space Technology, 2025)

Loss of circular EYA3 attenuates formaldehyde-induced cardiomyocyte pyroptosis and congenital heart defects by regulating Smad5 stability - Ying Zhang; Yanyan Yang; Xiangqin He; Pin Sun; Xiaoxia Song; Yu Tian; Jianmin Ma; Ruicong Sun; Tao Yu; Zhirong Jiang (Science of The Total Environment, 2025)

Enhanced deep eutectic solvent extraction of phenolic compounds from hawthorn seeds with ultrasonic and resin in-situ adsorption assistance: Process optimization, component analysis, and extraction mechanism - Pengfei Jiao; Xingmei He; Zhihao Zhou; Xuan Wang; Yunrui Zhang; Pin Chang; Xin Zhang; Peng Wang; Pengpeng Yang; Qiuhong Niu (Food Chemistry, 2025)

One-step controllable synthesis of N-doped porous carbon derived from ZIF-8 for efficient capacitive deionization - Pin Hou; Jiaqi Yan; Xiaoyu Yang; Ridha Djellabi; Xinrui Ge; Xinyu Sun; Jianli Jia; Jianbing Wang (Journal of Environmental Chemical Engineering, 2025)

Early diagenesis of coral rubble on the high-energy platform of Ximen Reef in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Shichen Tao; Xiyang Zhang; Hongqiang Yan; Zhiwei Hou; Ji Yang; Wenlong Jing; Pin Yan (Marine Geology, 2025)

Mapping Brain-Wide Neural Activity of Murine Attentional Processing in the Five-Choice Serial Reaction Time Task - Yin Yue; Youming Tan; Pin Yang; Shu Zhang; Hongzhen Pan; Yiran Lang; Zengqiang Yuan (Neuroscience Bulletin, 2025)

Cardiovascular dysfunction and altered lysosomal signaling in a murine model of acid sphingomyelinase deficiency - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Kiana Roudbari; Jenny Z. Hu; Saher A. Khan; Zhengchao Wang; Yangping Shentu; Mi Wang; Pin-Lan Li; Jiukuan Hao; Yang Zhang; et al. (Journal of Molecular Medicine, 2025)

Global research landscape and trends in Toxoplasma gondii from 2003 to 2022: A bibliometric analysis - Shi-Jie Fan; Ming Pan; Chen-Yang Xia; Pin Yang; Si-Yang Huang (Veterinary Parasitology, 2025)

Thermal-fluid coupled fracture behavior of fissured granite in a 3D crystal model - Heng Li; Sheng-Qi Yang; Bo-Wen Sun; Zhen Yang; Zhi-Jin Dong; Pin-Qiang Mo (Engineering Geology, 2025)

Sacrificial reduction effects derived inorganic-rich hybrid solid electrolyte interfaces for long-term and high reversibility aqueous zinc-ion batteries - Yu Chen; Jiahong Fan; Qian Li; Pin Yi; Houfu Tu; Dedong Shan; Wentao Wang; Shulin Zhao; Yang Zhang; Yuping Wu; Yuhui Chen; Dengji Xiao (Chemical Engineering Journal, 2025)

Validation of Automated Standardization Performance for ECDaim Software Developed Using a Taiwan-Specific Database - Yu-Ching Ni; Hui-Chieh Yang; Ing-Tsung Hsiao; Fan-Pin Tseng; Chia-Yu Lin; Wen-Bin Lin; Zong-Jhe Lyu (Journal of Medical and Biological Engineering, 2025)

Climate-controlled distribution of erosion over the Himalaya in the late Quaternary: Evidence from Sr-Nd isotope variability in paleo-Yamuna channel sediments - Mohd Amir; Debajyoti Paul; Shouye Yang; Yuan-Pin Chang (Quaternary Science Reviews, 2025)

Enrichment and characterization of foodborne fungal spores by ferric ion-based surface-assisted laser desorption/ionization mass spectrometry - Tzu-Ling Yang; Chih-Wei Chen; Noor Hidayat Abu Bakar; Pin-Chen Pan; Po-Hung Cheng; Yu-Chie Chen (Food Chemistry, 2025)

Oligosaccharide-assisted resolution of holothurian fucosylated chondroitin sulfate for fine structure and P-selectin inhibition - Ying Pan; Huifang Sun; Xi Gu; Sujuan Li; Shengtao Yang; Liang Zhang; Hui Mao; Pin Wang; Shasha Yang; Ronghua Yin; Zhili Zuo; Jinhua Zhao (Carbohydrate Polymers, 2025)

An optimized non-landslide sampling method for Landslide susceptibility evaluation using machine learning models - Shuai Xu; Yingxu Song; Pin Lu; Guizhen Mu; Ke Yang; Shangxiao Wang (Natural Hazards, 2025)

Associations between urinary multiple metal concentrations and mitochondrial DNA copy number among occupational workers - Zhiping Duan; Qinyu Zhang; Yiming Dai; Jiayun Ding; Changhao Cao; Qiang Hou; Ziqian Yang; Pin Sun; Jiming Zhang; Zhijun Zhou (International Archives of Occupational and Environmental Health, 2025)

Comprehensive interpretation of hillslope subsurface flow – An analytical approach to hillslopes with complex geometry - Bao-Ming Jin; Xin Yang; Kwan Tun Lee; Pin-Chun Huang; Peng Lin; Lanlan Gao; Lo-Ya Chen (Journal of Hydrology, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Theory and field tests of innovative cut blasting method for rock roadway excavation - Chengxiao Li; Renshu Yang; Jinjing Zuo; Pin Xie (Tunnelling and Underground Space Technology, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Microplastics accelerate nitrification, shape the microbial community, and alter antibiotic resistance during the nitrifying process - Yang Wang; Peikun Yuan; Pin Gao (Science of The Total Environment, 2025)

Iron/nitrogen/sulfur co-doped cyanobacteria derived carbon composites for enhanced hydroxychloroquine degradation via primary nonradical pathway in peroxymonosulfate-based fenton-like system - Tao Wang; Yuxuan Yang; Zheren Tang; Pin Zhao; Kunlun Yang; Xinhua Xu (Journal of Cleaner Production, 2025)

Rapid detection of colored and colorless macro- and micro-plastics in complex environment via near-infrared spectroscopy and machine learning - Hui-Huang Zou; Pin-Jing He; Wei Peng; Dong-Ying Lan; Hao-Yang Xian; Fan Lü; Hua Zhang (Journal of Environmental Sciences, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Rich molecular diversity of ribosomal RNA genes in Pseudo-nitzschia species (Bacillariophyceae) revealed through single-strain high throughput sequencing - Hui Wang; Kuiyan Liu; Ziyan He; Yang Chen; Chui Pin Leaw; Nansheng Chen (Algal Research, 2025)

Unveiling the interaction and combined effects of multiple metals/metalloids exposure to TNF-α and kidney function in adults using bayesian kernel machine regression and quantile-based G-computation - Kuei-Hau Luo; Hung-Pin Tu; Yong-Chuan Chung; Min-Hsin Huang; Chen-Cheng Yang; Tzu-Hua Chen; Cheng-Hong Yang; Hung-Yi Chuang (Journal of Trace Elements in Medicine and Biology, 2024)

Astragaloside IV alleviates diabetic nephropathy by modulating the gut-kidney axis and AMPK/PI3K/AKT pathway - Pin Gong; Hui Long; Qian Yang; Rui Zhou; Wenjuan Yang; Fuxin Chen; Jianwu Xie; Yanni Zhao; Hongbo Xu (Food Bioscience, 2024)

Emerging transition metal sulfide/MXene composites for the application of electrochemical energy storage - Xianghui Hu; Pin Ma; Zehao Zhang; Jian Wang; Cheng Li; Yee Sin Ang; Haibo Li; Hui Ying Yang (Chemical Engineering Journal, 2024)

Treatment of arsenic-contaminated groundwater with a novel iron oxide/carbon composite as the adsorbent - Hung-Hsiang Chen; Yu-Chen Chang; Wei-Kuo Wei; Yung-Pin Tsai; Chih-Chi Yang; Ku-Fan Chen (Water, Air, & Soil Pollution, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Bisphenol M inhibits mouse oocyte maturation in vitro by disrupting cytoskeleton architecture and cell cycle processes - Huilei Chen; Yang Liu; Yue Huang; Pin Zhang; Danli Du; Wenhua Yu; Caiyun Wu; Hongzhen Ruan; Ping Zhou; Zhiming Ding; Huifen Xiang (Reproductive Toxicology, 2024)

Geochemistry and zircon U-Pb geochronology of diabase, gabbros, anorthosites and ultramafic rocks from the South Andaman Island ophiolite suite on the South-Eastern margin of the Indian plate - Salim Akhtar; M. Santosh; Pin Gao; Cheng-Xue Yang; Ashima Saikia (Lithos, 2024)

Structural characterization and hypoglycemic activity of Cordyceps sinensis polysaccharide (CSP-3) - Pin Gong; Yingying Ke; Xiaojuan Wang; Hui Long; Wenjuan Yang; Jing Wang; Nan Li; Yanni Zhao; Fuxin Chen; Yuxi Guo (Food Bioscience, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Analytical solution for transient radial interaction between energy piles and soils: Thermo-elastic cavity expansion analysis - He Yang; Pei-Zhi Zhuang; Pin-Qiang Mo; Hai-Sui Yu; Xiaohui Chen (Geomechanics for Energy and the Environment, 2024)

Chromosome-Level Genome Assembly and Comparative Genomic Analysis of the Barbel Chub (Squaliobarbus curriculus) by Integration of PacBio Sequencing and Hi-C Technology - Baidong Zhang; Yanling Sun; Yang Liu; Xiaojun Song; Su Wang; Tiaoyi Xiao; Pin Nie (Fishes, 2024)
The barbel chub (Squaliobarbus curriculus), the only species in the genus, is widely distributed in freshwater lakes and rivers at different latitudes in East Asia, with fishery and biodiversity importance, and is an emerging commercially important fish in China. However, the resource of this species has dramatically declined due to anthropogenic activities such as over-exploitation, as well as water pollution. Genomic resources for S. curriculus are useful for the management and sustainable utilization of this important fish species, and also for a better understanding of its genetic variation in the region. Here, we report the chromosome-level assembly of the S. curriculus genome obtained from the integration of PacBio long sequencing and Hi-C technology. A total of 155.34 Gb high-quality PacBio sequences were generated, and the preliminary genome assembly was 894.95 Mb in size with a contig N50 being 20.34 Mb. By using Hi-C data, 99.42% of the assembled sequences were anchored to 24 pseudochromosomes, with chromosome lengths ranging from 27.22 to 58.75 Mb. A total of 25,779 protein-coding genes were predicted, 94.70% of which were functionally annotated. Moreover, S. curriculus shows resistance to grass carp haemorrhagic disease (GCHD) caused by grass carp reovirus (GCRV), which seriously hinders the status and future perspectives of commercial grass carp production. Phylogenetic analysis indicated that S. curriculus diverged with grass carp (Ctenopharyngodon idellus) approximately 20.80 million years ago. Annotations of the expanded gene families were found to be largely enriched in immune-related KEGG pathway categories. Moreover, a total of 18 Toll-like receptor (TLR) genes were identified from the whole genome of S. curriculus. The high-quality genome assembled in this study will provide a valuable resource for accelerating ecological, evolutionary, and genetic research on S. curriculus.

Casein/butyrylated dextrin nanoparticles and chitosan stabilized bilayer emulsions as fat substitutes in sponge cakes - Han Tao; Xiao-Han Fang; Pin Chen; Bao-Qiu Yang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

In situ semi-etching of bimetallic LDH nanosheet arrays into FeNi-LDH/MOF to boost oxygen evolution reaction - Hanli Qin; Jia Cheng; Pin Zhou; Zhenyuan Ji; Hongyuan Peng; Xiaoping Shen; Hu Zhou; Guoxing Zhu; Juan Yang (Chemical Engineering Journal, 2024)

Self-assembled complexing agent assisted chemical bath deposition of SnOX enabled highly efficient perovskite solar cells - Long Dong; Pin Lv; Benjia Zhu; Yanqing Zhu; Min Hu; Feifei Yang; Bo Zhang; Yi-Bing Cheng; Mi Xu; Jianfeng Lu (Chemical Engineering Journal, 2024)

Exosomes Derived from Irradiated-Prostate Cancer Cells Promote Cancer Progression - Chien‑Chih Ke; Chikondi Jassi; Chih-Hung Chuang; Chiung-Yuan Ko; Shu-Pin Huang; Shih-Hsun Kuo; Chia-Yang Li; Ya‑Ju Hsieh (Journal of Medical and Biological Engineering, 2024)

The mafic–ultramafic roots of a Mesoarchean microblock in southern India: Insights from petrochemistry and isotope geochronology of the Coorg Block - Cheng-Xue Yang; M. Santosh; Pin Gao; Y. Anilkumar; K.S. Anoop; Sung Won Kim; Sanghoon Kwon (Precambrian Research, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

MYPT1SMKO Mice Function as a Novel Spontaneous Age- and Hypertension-Dependent Animal Model of CSVD - Jian Chen; Cheng-Gang Li; Li-Xuan Yang; Yi Qian; Li-Wen Zhu; Pin-Yi Liu; Xiang Cao; Ye Wang; Min-Sheng Zhu; Yun Xu (Translational Stroke Research, 2024)

Mo, N co-doped cobalt hydroxide nanosheets for highly selective methanol-to-formate electrocatalytic conversion - Yaoxin Wu; Lili Ban; Hanzhen Wang; Qian Yang; Yaao Li; Ke Lu; Yuxiang Li; Pin Cui; Jinfeng Yang; Dalei Chang; Dezheng Yang; Feng Yu; et al. (Chemical Engineering Journal, 2024)

Biogeochemistry of sedimentary organic matter in the Yongjiang River estuary in the southern part of Hangzhou Bay, China, since the Late Pleistocene - Dongqin Huang; Xiaolong Li; Zilong Li; Pei Sun Loh; Jianxiong Hu; Jianfang Chen; Yuan-Pin Chang; Chin-Wen Yang; Qin Gao (Journal of Oceanology and Limnology, 2024)

Miocene lamprophyre and felsic volcanics in the outer zone of SW Japan: arc building through multiple sources in an active convergent margin - Pin Gao; M. Santosh; Toshiaki Tsunogae; Cheng-Xue Yang; M. Nakagawa; Sung Won Kim; Yunpeng Dong; Hai-Dong Liu (International Geology Review, 2024)

Extensive intragenomic variations of the 18S rDNA V4 region in the toxigenic diatom species Pseudo-nitzschia multistriata revealed through high-throughput sequencing - Hui Wang; Kuiyan Liu; Ziyan He; Yang Chen; Zhangxi Hu; Weizhou Chen; Chui Pin Leaw; Nansheng Chen (Marine Pollution Bulletin, 2024)

The establishment and evaluation of a swine model of deinagkistrodon acutus snakebite envenomation - Linjie Lai; Lutao Xie; Yi Chen; Wang Du; Xuelin Yang; Wanjuan Liu; Peixin Shangguan; Jiefeng Xu; Pin Lan (Toxicon, 2024)

A novel baking additive: Preparation, characterization, and application of chitosan hydrochloride/carboxymethyl starch sodium nano-gel for wheat bread - Xinlai Dou; Yanling Hao; Ying Sun; Pin Yang; Linlin Liu; Yinyuan He; Yanguo Shi; Chunhua Yang; Fenglian Chen (Food Hydrocolloids, 2024)

Exposure to pesticides and risk of colorectal cancer: A systematic review and meta-analysis - Pin-Peng Xie; Zhi-Qiang Zong; Jian-Chao Qiao; Zhuo-Yan Li; Cheng-Yang Hu (Environmental Pollution, 2024)

Economical-effective purification of brackish water through an integrated capacitive desalination & boron adsorption system - Liping Yang; Yixiang Li; Lu Guo; Pin Ma; Zhi Yi Leong; Jing Wang; Hui Ying Yang (Desalination, 2024)

Integrating water and insect pest management in agriculture - Po-An Lin; Sulav Paudel; Pin-Chu Lai; Raj K. GC; Dan-Hong Yang; Gary W. Felton (Journal of Pest Science, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

An overview of microplastic pollution in the environment over the megacity of Shanghai during 2013–2022 - Peikun Yuan; Yang Wang; Xiaoqian Chen; Pin Gao (Science of The Total Environment, 2024)

Bifunctional drug delivery system with carbonic anhydrase IX targeting and glutathione-responsivity driven by host-guest amphiphiles for effective tumor therapy - Jiawei Zhou; Yamin Li; Lutao Wang; Pin Lv; Miao Chen; Feijian Xiao; Tian Si; Jun Tao; Bo Yang (Carbohydrate Polymers, 2024)

Dual role of birnessite on the modulation of acid production and reinforcement of interspecific electron transfer in anaerobic digestion - Xinyu Yan; Lixiang Chen; Pin Peng; Fan Yang; Liping Dai; Han Zhang; Feng Zhao (Science of The Total Environment, 2024)

Efficient degradation of fluoroquinolone antibiotics in the landfill leachate by sludge biochar activated peracetic acid: Radical vs non-radical process - Zilin Zhou; Yan Yang; Gang Xue; Yang Yu; Jiabin Chen; Pin Gao; Yajie Qian (Chemical Engineering Journal, 2024)

Normal fault evolution in the Penghu Basin, a Paleogene Rift Basin in Western Taiwan Strait: A test of fault growth models - Pin-Rong Wu; Kenn-Ming Yang; Pin-Chi Wang; Chang-Jie Lee; Jong-Chang Wu (Tectonophysics, 2023)

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Using HPMC to improve sensory properties of vegan omelet analogue: Effect of HPMC on water retention, oil adsorption, and thermal gelation - Zhou Lu; Pin-Rou Lee; Hongshun Yang (Food Hydrocolloids, 2023)

Polymeric PDI-based photocatalytic nanoarchitectures promoting the performance of thin film composite membrane for forward osmosis water purification - Pin Zhao; Yang Hu; Xiaoqiang An; Rong Ji; Hao Liu; Hui Zhao; Weilong Song; Yuming Dong; Xinhua Wang (Chemical Engineering Journal, 2023)

Metal ion assistant transformation strategy to synthesize catechol-based metal–organic frameworks from Ti3C2T precursors - Weikang Wang; Yan Bai; Pin Yang; Shuai Yuan; Feiyang Li; Weiwei Zhao; Beibei Jin; Xuan Zhang; Shujuan Liu; Daqiang Yuan; Qiang Zhao (Science Bulletin, 2023)

Fluid migration patterns in shallow horizontal sand bodies pierced by vertical gas seepage in the Qiongdongnan Basin, South China Sea - Deng Wei; Liang Jinqiang; Yang Zhen; Kuang Zenggui; Yan Pin; Meng Miaomiao; Zhang Zijian (Journal of Asian Earth Sciences, 2023)

Kappa-carrageenan improves the gelation and structures of soy protein isolate through the formation of hydrogen bonding and electrostatic interactions - Zhou Lu; Pin-Rou Lee; Hongshun Yang (Food Hydrocolloids, 2023)

Identification of key precursors contributing to the formation of CX3R-type disinfection by-products along the typical full-scale drinking water treatment processes - Xu Yang; Shunke Ding; Rong Xiao; Pin Wang; Zhenqi Du; Ruihua Zhang; Wenhai Chu (Journal of Environmental Sciences, 2023)

The Coorg Block, southern India: Insights from felsic and mafic magmatic suites on Mesoarchean plate tectonics and correlation with supercontinent Ur - Cheng-Xue Yang; M. Santosh; Jarred C. Lloyd; Stijn Glorie; Pin Gao; Bing Yu; Y. Anilkumar; K.S. Anoop; Sung-Won Kim (Gondwana Research, 2023)

Rational targeting of autophagy in colorectal cancer therapy: From molecular interactions to pharmacological compounds - Canhui Jin; Tianbao Wang; Yanhui Yang; Pin Zhou; Juncheng Li; Wenhao Wu; Xin Lv; Guoqing Ma; Aihong Wang (Environmental Research, 2023)

Effects of Bacillus strain added as initial indigenous species into the biofloc system rearing Litopenaeus vannamei juveniles on biofloc preformation, water quality and shrimp growth - Hai-Hong Huang; Chao-Yun Li; Yan-Ju Lei; Bo-Lan Zhou; Wei-Qi Kuang; Wan-Sheng Zou; Pin-Hong Yang (Aquaculture, 2023)

Synergistic adsorption of surface-active components at the air-liquid interface improves foaming properties of plant-based egg analogues - Zhou Lu; Pin-Rou Lee; Hongshun Yang (Food Hydrocolloids, 2023)

Effect of starch addition on the physicochemical properties, molecular interactions, structures, and in vitro digestibility of the plant-based egg analogues - Zhou Lu; Yi Liu; Yi En Jayne Lee; Andrew Chan; Pin-Rou Lee; Hongshun Yang (Food Chemistry, 2023)

High-Fat Diet Exacerbates Autistic-Like Restricted Repetitive Behaviors and Social Abnormalities in CC2D1A Conditional Knockout Mice - Yu-Chiao Wang; Chin-Hao Chen; Cheng-Yi Yang; Pin Ling; Kuei-Sen Hsu (Molecular Neurobiology, 2023)

Cu/Al2O3 aerogels for high-efficiency and rapid iodide elimination from water - Xinyu Zhou; Pin Mao; Huiran Jin; Wanxia Huang; Aotian Gu; Kaiwei Chen; Shan Yun; Jing Chen; Yi Yang (Journal of Hazardous Materials, 2023)

Thiobacillus spp. and Anaeromyxobacter spp. mediate arsenite oxidation-dependent biological nitrogen fixation in two contrasting types of arsenic-contaminated soils - Yongbin Li; Lifang Guo; Rui Yang; Zhaohui Yang; Haihan Zhang; Qiqian Li; Zhiguo Cao; Xin Zhang; Pin Gao; Wenlong Gao; Geng Yan; Duanyi Huang; et al. (Journal of Hazardous Materials, 2023)

Occurrence, spatial distribution, and sources of PFASs in the water and sediment from lakes in the Tibetan Plateau - Yu Chen; Lijia Wei; Wei Luo; Ning Jiang; Yali Shi; Pin Zhao; Bila Ga; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang (Journal of Hazardous Materials, 2023)

A novel Cu nanoporous aerogel for high-efficient immobilization of iodide in water - Xinyu Zhou; Huiran Jin; Shan Yun; Wanxia Huang; Pin Mao; Jing Chen; Yi Yang (Chemical Engineering Journal, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Geomorphic development of an unvegetated shingle cay on the Ximen Reef in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Lirong Wang; Xiyang Zhang; Xiaoju Liu; Fei Tan; Pin Yan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Hypervalent potassium xanthate modified SnO2 for highly efficient perovskite solar modules - Pin Lv; Yufei Yang; Neng Li; Yuxi Zhang; Min Hu; Bo Huang; Yanqing Zhu; Yulong Wang; Junye Pan; Shifeng Wang; Bo Zhang; Fuzhi Huang; et al. (Chemical Engineering Journal, 2023)

Fabrication of a core-shell porphyrin-based magnetic covalent organic framework for effective extraction of PCPs in a wide polarity range - Tao Ning; Siyuan Di; Zihan Li; Haokun Zhang; Zhangdi Peng; Hucheng Yang; Pin Chen; Yue Bao; Yixin Zhai; Shukui Zhu (Analytica Chimica Acta, 2023)

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

CDK1 promotes the proliferation of melanocytes in Rex rabbits - Yingying Dai; Shuaishuai Hu; Shaocheng Bai; Jiali Li; Naisu Yang; Pin Zhai; Bohao Zhao; Yang Chen; Xinsheng Wu (Genes & Genomics, 2022)

Optimal Design of the Seepage Control for Xianglushan Diversion Tunnel Under High External Water Pressure - Zhen-jie Zhang; Chun-pin Zeng; Hu Li; Yang Gao; Liang Gong; Yu-xing Li; Hai-fang Liang; En-zhong Zhang (Geotechnical and Geological Engineering, 2022)

Effects of perfluorooctanoic acid (PFOA) on activated sludge microbial community under aerobic and anaerobic conditions - Duanyi Huang; Rui Xu; Xiaoxu Sun; Yongbin Li; Enzong Xiao; Zhimin Xu; Qi Wang; Pin Gao; Zhaohui Yang; Hanzhi Lin; Weimin Sun (Environmental Science and Pollution Research, 2022)

Paleolimnological evidence for lacustrine environmental evolution and paleo-typhoon records during the late Holocene in eastern Taiwan - Liang-Chi Wang; Yu-Min Chou; Huei-Fen Chen; Yuan-Pin Chang; Hong-Wei Chiang; Tien-Nan Yang; Liang-Jian Shiau; Yue-Gau Chen (Journal of Paleolimnology, 2022)

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis - Rui Xu; Xiaoxu Sun; Max M. Häggblom; Yiran Dong; Miaomiao Zhang; Zhaohui Yang; Enzong Xiao; Tangfu Xiao; Pin Gao; Baoqin Li; Weimin Sun (Environmental Microbiology, 2022)
Summary The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal‐rich environments. Metagenomic binning reconstructed 29 high‐quality metagenome‐assembled genomes (MAGs) associated with Acidobacteriia , providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, suggesting the potential of Acidobacteriia to transform such metal(loid)s. Additionally, genes associated with alleviation of acidic and metal stress were also detected in these MAGs. Acidobacteriia may have the capabilities to resist or transform metal(loid)s in acidic metal‐contaminated sites. Moreover, these genes encoding metal transformation could be also identified in the Acidobacteriia ‐associated MAGs from five additional metal‐contaminated sites across Southwest China, as well as Acidobacteriia ‐associated reference genomes from the NCBI database, suggesting that the capability of metal transformation may be widespread among Acidobacteriia members. This discovery provides an understanding of metabolic potentials of the Acidobacteriia in acidic metal‐rich sites.

Steroid Receptor Coactivator 3 Regulates Synaptic Plasticity and Hippocampus-dependent Memory - Hai-Long Zhang; Bing Zhao; Pin Yang; Yin-Quan Du; Wei Han; Jianming Xu; Dong-Min Yin (Neuroscience Bulletin, 2021)
Steroid hormones play important roles in brain development and function. The signaling of steroid hormones depends on the interaction between steroid receptors and their coactivators. Although the function of steroid receptor coactivators has been extensively studied in other tissues, their functions in the central nervous system are less well investigated. In this study, we addressed the function of steroid receptor coactivator 3 (SRC3) – a member of the p160 SRC protein family that is expressed predominantly in the hippocampus. While hippocampal development was not altered in Src3 +/− mice, hippocampus-dependent functions such as short-term memory and spatial memory were impaired. We further demonstrated that the deficient learning and memory in Src3 +/− mice was strongly associated with the impairment of long-term potentiation (LTP) at Schaffer Collateral-CA1 synapses. Mechanistic studies indicated that Src3 +/− mutation altered the composition of N-methyl-D-aspartate receptor subunits in the postsynaptic densities of hippocampal neurons. Finally, we showed that SRC3 regulated synaptic plasticity and learning mainly dependent on its lysine acetyltransferase activity. Taken together, these results reveal previously unknown functions of SRC3 in the hippocampus and thus may provide insight into how steroid hormones regulate brain function.

Magnetic porous biochar as a renewable and highly effective adsorbent for the removal of tetracycline hydrochloride in water - Hucheng Yang; Hao Yu; Jiahao Wang; Tao Ning; Pin Chen; Jing Yu; Siyuan Di; Shukui Zhu (Environmental Science and Pollution Research, 2021)

Substrate damage and recovery after giant clam shell mining at remote coral reefs in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Xiyang Zhang; Xiaoju Liu; Fei Tan; Pin Yan (Journal of Geographical Sciences, 2021)

Three-dimensional Spheroid Culture Enhances Multipotent Differentiation and Stemness Capacities of Human Dental Pulp‐derived Mesenchymal Stem Cells by Modulating MAPK and NF-kB Signaling Pathways - Ya-Hui Chan; Yu-Chieh Lee; Chia-Yi Hung; Pi-Ju Yang; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2021)

Strong in vitro and in vivo cytotoxic effects of two platinum(II) complexes with cryptolepine derivatives - Li-Qin Qin; Zu-Zhuang Wei; Lin Yang; Qi-Pin Qin; Jia-Jing Zeng; Ming-Xiong Tan; Hong Liang (Medicinal Chemistry Research, 2021)

Multimodal Image Analysis of Sexual Dimorphism in Developing Childhood Brain - Xiujun Yang; Aojie Li; Lihong Li; Tingting Li; Pin Li; Manhua Liu (Brain Topography, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

First Detection and Molecular Identification of Entamoeba in Yaks from China - Mei Ren; Fan Yang; Jing-min Gou; Pin-xue Wang; Min Zou; Xiao-hong Zhong; Qing Lin (Acta Parasitologica, 2021)

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

Feasibility of using bed filters packed with rice-straw-based activated carbon and selected biomass waste for the control of frying fume exhaust - Yen-Chi Chen; Xuan-En Yang; Kun-Yi Lin; Wei-Wen Huang; Chi-Chi Lin; Kuo-Pin Yu (Environmental Science and Pollution Research, 2020)

Fixed-bed adsorption of copper from aqueous media using chitosan-coated bentonite, chitosan-coated sand, and chitosan-coated kaolinite - Cybelle M. Futalan; Jung-Hung Yang; Piaw Phatai; I-Pin Chen; Meng-Wei Wan (Environmental Science and Pollution Research, 2020)

Seasonal and diurnal variations of greenhouse gas emissions from a saline mangrove constructed wetland by using an in situ continuous GHG monitoring system - Cheng-Pin Tsai; Ching-Mei Huang; Chung-Shin Yuan; Lei Yang (Environmental Science and Pollution Research, 2020)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

LncRNA TUG1 promoted osteogenic differentiation through promoting bFGF ubiquitination - Yang Yu; Ying Chen; Yi-jing Zheng; Qi-hao Weng; Si-pin Zhu; Dong-sheng Zhou (In Vitro Cellular & Developmental Biology - Animal, 2020)

Non-radical activation of H2O2 by surface-disordered WO3 for efficient and selective pollutant degradation with weak matrix effects - Ai-Yong Zhang; Pin-Cheng Zhao; Yuan-Yi He; Yang Zhou; Jing-Wei Feng (Environmental Science and Pollution Research, 2020)

Correction to: Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

LpxD gene knockout elicits protection to Litopenaeus vannamei, white shrimp, against Vibrio parahaemolyticus infection - Ching-Yi Tsai; Harvey M. Santos; Shao-Yang Hu; Cheng Yu Sang; Ciara Alyssa S. Yanuaria; Ernest Nicolo G. Lola; Lemmuel L. Tayo; Karmella Marie A. Nitura; Chun Hung Liu; Kuo Pin Chuang (Aquaculture International, 2019)

The application of forward osmosis for simulated surface water treatment by using trisodium citrate as draw solute - Shihui Yang; Baoyu Gao; Pin Zhao; Chen Wang; Xue Shen; Qinyan Yue; Ho kyong Shon (Environmental Science and Pollution Research, 2019)

Flavobacterium sharifuzzamanii sp. nov., Isolated from the Sediments of the East China Sea - Sanjit C. Debnath; Can Chen; Shu-Xia Liu; Ya-Nan Di; Dao-Qiong Zheng; Xin-Yang Li; Xue-Wei Xu; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2019)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

Spatial and temporal variation of H and O isotopic compositions of the Xijiang River system, Southwest China - Guilin Han; Pin Lv; Yang Tang; Zhaoliang Song (Isotopes in Environmental and Health Studies, 2018)

Spatiotemporal patterns of drought at various time scales in Shandong Province of Eastern China - Depeng Zuo; Siyang Cai; Zongxue Xu; Fulin Li; Wenchao Sun; Xiaojing Yang; Guangyuan Kan; Pin Liu (Theoretical and Applied Climatology, 2018)

Transcriptome comparative analysis of two Camellia species reveals lipid metabolism during mature seed natural drying - Jin-Ling Feng; Zhi-Jian Yang; Wei-Wei Bai; Shi-Pin Chen; Wen-Qiang Xu; Yousry A. El-Kassaby; Hui Chen (Trees, 2017)

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

Signaling pathway in development of Camellia oleifera nurse seedling grafting union - Jin-Ling Feng; Zhi-Jian Yang; Shi-Pin Chen; Yousry A. El-Kassaby; Hui Chen (Trees, 2017)

Characterization of extracellular polymeric substances in biofilms under long-term exposure to ciprofloxacin antibiotic using fluorescence excitation-emission matrix and parallel factor analysis - Chaochao Gu; Pin Gao; Fan Yang; Dongxuan An; Mariya Munir; Hanzhong Jia; Gang Xue; Chunyan Ma (Environmental Science and Pollution Research, 2017)

Comparison of two modified coal ash ferric-carbon micro-electrolysis ceramic media for pretreatment of tetracycline wastewater - Kunlun Yang; Yang Jin; Qinyan Yue; Pin Zhao; Yuan Gao; Suqing Wu; Baoyu Gao (Environmental Science and Pollution Research, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Contribution of redox-dependent activation of endothelial Nlrp3 inflammasomes to hyperglycemia-induced endothelial dysfunction - Yang Chen; Lei Wang; Ashley L. Pitzer; Xiang Li; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2016)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Highly stable rice-straw-derived charcoal in 3700-year-old ancient paddy soil: evidence for an effective pathway toward carbon sequestration - Mengxiong Wu; Min Yang; Xingguo Han; Ting Zhong; Yunfei Zheng; Pin Ding; Weixiang Wu (Environmental Science and Pollution Research, 2016)

Acid sphingomyelinase inhibition protects mice from lung edema and lethal Staphylococcus aureus sepsis - Huiming Peng; Cao Li; Stephanie Kadow; Brian D. Henry; Jörg Steinmann; Katrin Anne Becker; Andrea Riehle; Natalie Beckmann; Barbara Wilker; Pin-Lan Li; Timothy Pritts; Michael J. Edwards; et al. (Journal of Molecular Medicine, 2015)

The versatile roles of CARDs in regulating apoptosis, inflammation, and NF-κB signaling - Wen-Pin Kao; Chao-Yu Yang; Tsung-Wei Su; Yin-Ting Wang; Yu-Chih Lo; Su-Chang Lin (Apoptosis, 2015)

Global patterns of soil microbial nitrogen and phosphorus stoichiometry in forest ecosystems - Pin Li; Yuanhe Yang; Wenxuan Han; Jingyun Fang (Global Ecology and Biogeography, 2014)
Aim To investigate broad‐scale patterns of soil microbial nitrogen ( N ) and phosphorus ( P ) stoichiometry and their environmental drivers. Location Global forests. Methods By synthesizing 652 observations of soil microbial biomass N and P derived from the published literature, we investigated global patterns of soil microbial N , P and N : P ratios and their relationships with climate, soil and vegetation types. Results Microbial N and P concentrations varied widely among forest types, with relatively low N and P concentrations but high N : P ratios in tropical forests. The N and P concentrations increased and the N : P ratio decreased with increasing latitude (or decreasing temperature). The N:P ratio showed a similar pattern along the precipitation gradient to that along the temperature gradient, whereas microbial N and P displayed weak trends along the precipitation gradient. Edaphic variables also regulated the patterns of microbial N and P stoichiometry: microbial N and P concentrations increased with soil N and P concentrations as well as with soil pH . Mixed‐effects models revealed that edaphic factors explained the largest part of the variation in microbial N , P and the N : P ratio, suggesting their dominant role. Main conclusions Our findings highlight that there are broad‐scale patterns in microbial N , P and the N : P ratio along the gradients of latitude, temperature and precipitation, which are similar to those reported in plants and soils. The consistency of these patterns in plant–soil–microbe ecosystems supports the hypothesis that P is more often the major limiting element at low latitudes than at high latitudes.

Application of AVO analysis to gas hydrates identification in the northern slope of the South China Sea - Rui Yang; Pin Yan; Nengyou Wu; Zhibin Sha; Jinqiang Liang (Acta Geophysica, 2014)

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

Increased topsoil carbon stock across China's forests - Yuanhe Yang; Pin Li; Jinzhi Ding; Xia Zhao; Wenhong Ma; Chengjun Ji; Jingyun Fang (Global Change Biology, 2014)
Biomass carbon accumulation in forest ecosystems is a widespread phenomenon at both regional and global scales. However, as coupled carbon–climate models predicted, a positive feedback could be triggered if accelerated soil carbon decomposition offsets enhanced vegetation growth under a warming climate. It is thus crucial to reveal whether and how soil carbon stock in forest ecosystems has changed over recent decades. However, large‐scale changes in soil carbon stock across forest ecosystems have not yet been carefully examined at both regional and global scales, which have been widely perceived as a big bottleneck in untangling carbon–climate feedback. Using newly developed database and sophisticated data mining approach, here we evaluated temporal changes in topsoil carbon stock across major forest ecosystem in China and analysed potential drivers in soil carbon dynamics over broad geographical scale. Our results indicated that topsoil carbon stock increased significantly within all of five major forest types during the period of 1980s–2000s, with an overall rate of 20.0 g C m −2 yr −1 (95% confidence interval, 14.1–25.5). The magnitude of soil carbon accumulation across coniferous forests and coniferous/broadleaved mixed forests exhibited meaningful increases with both mean annual temperature and precipitation. Moreover, soil carbon dynamics across these forest ecosystems were positively associated with clay content, with a larger amount of SOC accumulation occurring in fine‐textured soils. In contrast, changes in soil carbon stock across broadleaved forests were insensitive to either climatic or edaphic variables. Overall, these results suggest that soil carbon accumulation does not counteract vegetation carbon sequestration across China's forest ecosystems. The combination of soil carbon accumulation and vegetation carbon sequestration triggers a negative feedback to climate warming, rather than a positive feedback predicted by coupled carbon–climate models.

Control of autophagy maturation by acid sphingomyelinase in mouse coronary arterial smooth muscle cells: protective role in atherosclerosis - Xiang Li; Ming Xu; Ashley L. Pitzer; Min Xia; Krishna M. Boini; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2014)

Nod-Like Receptor Protein 1 Inflammasome Mediates Neuron Injury under High Glucose - Xian-Fang Meng; Xiao-Lan Wang; Xiu-Juan Tian; Zhi-Hua Yang; Guang-Pin Chu; Jing Zhang; Man Li; Jing Shi; Chun Zhang (Molecular Neurobiology, 2014)

Fluid inclusion and H–O–C isotope geochemistry of the Yaochong porphyry Mo deposit in Dabie Shan, China: a case study of porphyry systems in continental collision orogens - Pin Wang; Yan-Jing Chen; Bin Fu; Yong-Fei Yang; Mei Mi; Zhong-Lie Li (International Journal of Earth Sciences, 2014)

APPLICATION OF A DECISION SUPPORT SYSTEM TO SUSTAINABLE LOWLAND PLANNING AND MANAGEMENT IN YUNLIN AREA, TAIWAN - Hsiao‐Wen Wang; Chun‐Yao Yang; Pin‐Han Kuo (Irrigation and Drainage, 2013)
Sustainable approaches are recognized as a necessity for lowland planning and management. The spatial dimension of sustainability engages relations between different land uses, ecosystems, and human effects at different scales and over time. Yunlin County, located in south‐western Taiwan, has abundant natural resources but has been suffering from flooding and land subsidence for a long time. With the effects of climate change, lowland management in this area is becoming complicated. Possible strategies should thus be considered and conveyed to decision‐makers in the most efficient and transparent way, so as to redirect further discussion towards the conflicting aspects. The study evaluated the possible consequences of three planning scenarios on safety, economic, and ecological resources as a whole based on the future developing trend. The scenarios were then compared by applying OSIRIS, a decision and evaluation support system, to highlight the conflicting sites and to propose an optimal strategy. The results illustrated that the current lowland management policy is not effective and sustainable. Instead, the Coastal Conservation Green Way scenario might not only ease flood threat but also provide ecological benefit. The study could thus contribute to enhanced communication between stakeholders and help achieve sustainable lowland management. Copyright © 2013 John Wiley & Sons, Ltd.

TRAIL death receptor 4 signaling via lysosome fusion and membrane raft clustering in coronary arterial endothelial cells: evidence from ASM knockout mice - Xiang Li; Wei-Qing Han; Krishna M. Boini; Min Xia; Yang Zhang; Pin-Lan Li (Journal of Molecular Medicine, 2013)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

APPLICATION OF LANDSCAPE ECOLOGICAL DECISION AND EVALUATION SUPPORT SYSTEM ON FLOOD MITIGATION STRATEGIES - Chun‐Yao Yang; Hsiao‐Wen Wang; Pin‐Han Kuo (Irrigation and Drainage, 2011)
While flood mitigation measures are needed in flood‐prone areas, some may impact the environment, for example by causing habitat fragmentation. As flooding issues nowadays are more complicated and should be discussed taking multidisciplinary considerations into account, the purpose of this study was to evaluate the effects of land use changes on flooding, landscape pattern, and ecological resources as a whole, based on past environmental changes and trends in future development, using the concept of the Landscape Ecological Decision and Evaluation Support System Model (LEDESS). Yunlin County, one of the demonstration sites of the Regulation Project of Flood‐Prone Areas, proposed by the Water Resource Agency of Taiwan in 2005, was studied. We designed three scenarios, i.e. Scenario A for the current situation, Scenario B for the government policy, and Scenario C as a sustainable policy integrating room for water. We used people, planet, and profit as the indicators to understand the consequences under different scenarios. The results indicated that lots of land will be abandonedin the near future due to flooding regardless of whether or not mitigation measures are adopted. That is to say, the coastal area will turn into a wetland area through natural processes. Hence, we need to reconsider land use strategy. Copyright © 2011 John Wiley & Sons, Ltd.

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Detection and identification of a new phytoplasma associated with periwinkle leaf yellowing disease in Taiwan - Wuu-Yang Chen; Yao-Chen Huang; Meng-Lu Tsai; Chan-Pin Lin (Australasian Plant Pathology, 2011)

Prazosin induces p53-mediated autophagic cell death in H9C2 cells - Yi-Fan Yang; Chau-Chung Wu; Wen-Pin Chen; Yuh-Lien Chen; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

A novel strategy to derive iPS cells from porcine fibroblasts - WeiMin Ruan; JianYong Han; Pin Li; SuYing Cao; Yang An; Bing Lim; Ning Li (Science China Life Sciences, 2011)

Rescue of Newcastle disease virus from cloned cDNA using an RNA polymerase II promoter - Bao-yu Li; Xue-rui Li; Xi Lan; Xiang-pin Yin; Zhi-yong Li; Bin Yang; Ji-xing Liu (Archives of Virology, 2011)

Construction and Characterization of a Bacterial Artificial Chromosome (BAC) Library of Pacific White Shrimp, Litopenaeus vannamei - Xiaojun Zhang; Yang Zhang; Chantel Scheuring; Hong-Bin Zhang; Pin Huan; Bing Wang; Chengzhang Liu; Fuhua Li; Bin Liu; Jianhai Xiang (Marine Biotechnology, 2010)

Transforming growth factor-β type I receptor/ALK5 contributes to doxazosin-induced apoptosis in H9C2 cells - Yi-Fan Yang; Chau-Chung Wu; Wen-Pin Chen; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Isolation and characterization of 30 novel polymorphic microsatellite loci from Japanese halfbeak, Hyporhamphus sajori (Temminck et Schlegel, 1846) - Shi-Chao Xing; Gen-Bo Xu; Guan-Pin Yang; Shan-Shan Liu; Xiao-Lin Liao; Yong-sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

Twelve polymorphic microsatellite loci from a dinucleotide-enriched genomic library of Japanese Spanish mackerel (Scomberomorus niphonius) - Shi-Chao Xing; Gen-Bo Xu; Xiao-Lin Liao; Guan-Pin Yang; Song-Lin Chen (Conservation Genetics, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Cell Type-Specific Targeting with Surface-Engineered Lentiviral Vectors Co-displaying OKT3 Antibody and Fusogenic Molecule - Haiguang Yang; Kye-Il Joo; Leslie Ziegler; Pin Wang (Pharmaceutical Research, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Construction and Characterization of Two Bacterial Artificial Chromosome Libraries of Zhikong Scallop, Chlamys farreri Jones et Preston, and Identification of BAC Clones Containing the Genes Involved in Its Innate Immune System - Yang Zhang; Xiaojun Zhang; Chantel F. Scheuring; Hong-Bin Zhang; Pin Huan; Fuhua Li; Jianhai Xiang (Marine Biotechnology, 2008)

Molecular modeling of zinc and copper binding with Alzheimer’s amyloid β-peptide - Daxiong Han; Haiyan Wang; Pin Yang (BioMetals, 2008)

Breeding of an elite Laminaria variety 90-1 through inter-specific gametophyte crossing - Quan-Sheng Zhang; Xue-Xi Tang; Yi-Zhou Cong; Shan-Cun Qu; Shi-Ju Luo; Guan-Pin Yang (Journal of Applied Phycology, 2007)

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

Double-strand hydrolysis of DNA by a magnesium(II) complex with diethylenetriamine - Pin Yang; Rui Ren; Maolin Guo; Aixin Song; Xiangli Meng; Caixia Yuan; Qinghua Zhou; Huili Chen; Zhenhai Xiong; Xiaoli Gao (JBIC Journal of Biological Inorganic Chemistry, 2004)

Study on business pollution and its countermeasures in Shanghai - Kai Yang; Yun Wang; Xiangnan Gan; Pin Gu (Chinese Geographical Science, 1997)